Sexual Reproduction in Dinoflagellates—The Case of Noctiluca scintillans and Its Ecological Implications - Lee, Jeffery Liang-Neng; Chiang, Kuo-Ping; Tsai, Sheng-Fang (Frontiers in Marine Science, 2021)
Noctiluca scintillans is a larger, bioluminescent red-tide dinoflagellate (400–1,000 μm in diameter) that reproduces by sexual or asexual reproduction (binary fission). The process of sexual reproduction in N. scintillans has been thoroughly studied, but the ecological role and the mechanism of shifting from asexual to sexual reproduction have not been fully elucidated. It is believed, however, that sexual reproduction occurs when N. scintillans faces environmental stress. In this study, we tried to determine which factors drive N. scintillans to undergo sexual reproduction and we considered sexual reproduction’s ecological role. We cultured N. scintillans under different conditions of temperature, N. scintillans cell concentration, prey concentration, cultivation time, cultivation volume, light exposure time and physical vibration (simulated wave motion), and counted gametocyte mother cells every 24 h to calculate how the sexual reproduction rate changed over the experimental period. Rises in the sexual reproduction rate or the concentration of gametocyte mother cells only occurred in response to large variations in prey concentration, typically after the exponential phase of N. scintillans population growth. A noticeable upsurge in gametocyte mother cells, from 1% or less to nearly 10% of the total N. scintillans population, occurred when the prey concentration fell below ∼400 cells/mL. This implies that a sudden decrease in prey concentration induces more N. scintillans to shift from trophonts to gametocyte mother cells. We suggest that sexual reproduction may occur in N. scintillans as a response to the post-bloom situation when the dinoflagellate’s food supply has been dramatically depleted, producing large numbers of gametes for an alternative mode of survival after the end of each bloom.